KEJADIAN STUNTING DAN KEMATANGAN USIA TULANG PADA ANAK USIA SEKOLAH DASAR DI DAERAH PERTANIAN KABUPATEN BREBES (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
AbstrakPestisida merupakan salah satu EDCs. Penelitian ini bertujuan menggambarkan kejadian stunting dan kematangan usia tulang pada anak usia Sekolah Dasar di Daerah Pertanian Kabupaten Brebes. Penelitian observasional tahun 2015 dengan pendekatan cross sectional. Sampel 66 siswa SD Dukuhlo 01 dan 02 berusia 8-12 tahun. Analisis statistik menggunakan uji chi-square. Kejadian stunting sebanyak 21,2% dan siswa yang mengalami keterlambatan usia tulang sebanyak 42,4%. Proporsi siswa metabolit pestisida positif lebih banyak pada yang terlibat kegiatan pertanian (29,2%) dibanding siswa yang tidak terlibat kegiatan pertanian (5,6%). Kejadian stunting lebih banyak pada siswa dengan metabolit pestisida positif (26,7%) dibanding yang negatif (19,6%). Siswa kategori terlambat usia tulangnya lebih banyak pada yang metabolit pestisida positif (46,7%) dibanding yang negatif (41,2%). Kejadian stunting lebih banyak pada siswa dengan ke terlambatan usia tulang (42,9%) dibanding siswa yang usia tulangnya termasuk kategori normal (5,3%) dan berhubungan bermakna (p=0,001).Kata kunci : stunting, usia tulang, pestisida, anak SD, daerah pertanian. AbstractPesticide is an example of EDCs source. This study aimed to describe prevalence of stunting and bone-age maturity in elementary school students in agriculture areas of Brebes Districts. This was an observational study conducted in 2015 with cross sectional approach. Study subjects consisted of 66 students of SD Dukuhlo 01 and 02, ranged from 8 to12 years old. chi-square test was used to analyzed the data. This study showed stunting prevalence among students was 21.2%. There were 42.4% students underwent delayed bone-age maturiey. Proportion of students with positive pesticide metabolites were higher in those who involved in agriculture activities (29.2%) compared to those who did not (5.6%). Stunting was more prevalent in students with positive pesticide metabolites (26.7%) compared to the negative ones (19.6%). Students with delayed bone-age maturity were more frequent to be found with positive pesticide metabolites (46.7%) compared to negative (41.2%). Proportion of students with delayed bone-age maturiry (42.9%) compared to normal (5,3%). Stunting were significantly related to delayed bone-age maturity (p=0.001).Keyword : Stunting; Bone-age; Esticide; Elementary school students; Agricultural area.